Characterizing transcripts of HIV-1 different substrains using direct RNA sequencing - Weizhen Li; Yong Huang; Haowen Yuan; Jingwan Han; Zhengyang Li; Aiping Tong; Yating Li; Hanping Li; Yongjian Liu; Lei Jia; Xiaolin Wang; Jingyun Li; et al. (Heliyon)
Post-transcriptional processing and modification of viral RNA, including alternative splicing, polyadenylation, and methylation, play crucial roles in regulating viral gene expression, enhancing genomic stability, and increasing replication efficiency. These processes have significant implications for viral biology and antiviral therapies. In this study, using Oxford Nanopore Technology (ONT) direct RNA sequencing (DRS), we provided a comprehensive analysis of the transcriptome and epitranscriptome features of the HIV-1 B (NL4-3) subtype strain and, for the first time, characterized these features in the CRF01_AE (GX2005002) subtype strain. We identified 11 novel splicing sites among the 61 RNA isoforms in NL4-3 and defined the splicing sites for GX2005002 based on its 63 RNA isoforms. Furthermore, we identified 74 and 79 chemically modified sites in the transcripts of NL4-3 and GX2005002, respectively. Although differences in poly(A) tail length were observed between the two HIV-1 strains, no specific correlation was detected between poly(A) tail length and the number of modification sites. Additionally, three distinct N6-methyladenosine (m6A) modification sites were identified in both NL4-3 and GX2005002 transcripts. This study provides a detailed analysis of post-transcriptional processing modifications in HIV-1 and suggests promising avenues for future research that could potentially be applied as new therapeutic targets in HIV treatment.